Highly Selective Catalytic Hydrogenation and Etherification of 5-Hydroxymethyl-2-furaldehyde to 2,5-Bis(alkoxymethyl)furans for Potential Biodiesel Production - Han, Jusung; Kim, Yo-Han; Jung, Byeong Yeon; Hwang, Seung Hyun; Jegal, Jonggon; Kim, Jung Won; Lee, Yoon-Sik (Synlett, 2017)
5-Hydroxymethyl-2-furaldehyde (HMF) was hydrogenated to 2,5-bis(hydroxymethyl)furan (BHMF) in various n-alcohol solvents with more than 99% yield using Ru(OH)x/ZrO2 catalyst. The BHMF in the same solvents was subsequently etherified to give 2,5-bis(alkoxymethyl)furans (BAMFs, four examples) as potential biodiesels with moderate to good yields using Amberlyst-15.
Keywords: hydrogenation; biomass; ruthenium; biofuels; etherification